2021
DOI: 10.1038/s41598-021-95410-y
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor strongly affects epithelial Na+ transport and barrier function in fetal alveolar cells, with minor sex-specific effects

Abstract: Male sex remains an independent risk factor for respiratory distress syndrome (RDS) in preterm infants. Insufficient Na+ transport-mediated alveolar fluid clearance contributes to RDS development and we previously demonstrated sex-specific differences in Na+ transport. The epidermal growth factor (EGF) is important during fetal lung development with possible influence on Na+ transport. Sex-specific effects of EGF during surfactant synthesis were shown. We thus determined whether EGF exerts sex-specific effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Other studies have reported sex-specific pollution effects on lung function and cytokines in primates and humans [ 68 , 69 , 70 , 71 ], and rank operates very differently in male primates (i.e., males physically fight to establish and re-establish rank, and mid-ranked males, often in conflict with animals both above and below them, display particularly high social vigilance [ 72 ] and plasma vasopressin [ 73 ]. Likewise, lung development, function, and volume vary by sex in human [ 74 , 75 , 76 ] and animal populations; one human study found that maternal and early-life stress reduced postnatal lung function among boys but not girls [ 71 ]. In mice, males have been shown more sensitive to in-utero second-hand smoke exposure than females during lung development [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported sex-specific pollution effects on lung function and cytokines in primates and humans [ 68 , 69 , 70 , 71 ], and rank operates very differently in male primates (i.e., males physically fight to establish and re-establish rank, and mid-ranked males, often in conflict with animals both above and below them, display particularly high social vigilance [ 72 ] and plasma vasopressin [ 73 ]. Likewise, lung development, function, and volume vary by sex in human [ 74 , 75 , 76 ] and animal populations; one human study found that maternal and early-life stress reduced postnatal lung function among boys but not girls [ 71 ]. In mice, males have been shown more sensitive to in-utero second-hand smoke exposure than females during lung development [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Reverse transcription was carried out employing the Maxima H Minus DNA Synthesis Kit (Thermo Fisher Scientific). Real-time quantitative PCR (RT-qPCR) was performed in the CFX 96 Real-Time system (Bio-Rad, Munich, Germany) using the SYBR Select Master Mix (Fisher Scientific GmbH) and gene-specific primers [ 41 , 42 ] as described before [ 42 ]. The resulting molecule concentrations were normalized to a reference gene encoding for the mitochondrial ribosomal protein S18a (Mrps18a).…”
Section: Methodsmentioning
confidence: 99%
“…As discussed above, sex differences in EGF and GC signaling have been noted. Analyzing their effect on Na + transport demonstrated that chronic EGF treatment reduced ENaC mRNA levels and activity in both male and female FDLE cells [179]. In contrast, acute effects of EGF were sex-specific with a reduced Na + transport observed only in male FDLE cells [179].…”
Section: Alveolar Fluid Clearancementioning
confidence: 98%